Tusalama’: Nilai Karakter Damai Syekh Yusuf Perspektif Lontaraq Gowa dan Implikasi terhadap Bimbingan Konseling - Muh. Syawal Hikmah; Moh. Mirdan; Muhammad Silmi Kaffah; Akbar Gibran Yusri; A. As'ad Fathan; Alfin Elkindy Amsil (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2025)
The purpose of this reserch is to explore the values of peace-oriented character in the life history of Syekh Yusuf Al-Makassari from the perspective of Lontaraq Gowa, and to examine how these character values imply for guidance and counseling practices. This research employs a qualitative approach using the Gadamerian hermeneutic method, which emphasizes the analytical process between the parts and the whole in the effort to understand and interpret texts meaningfully. The findings of this reserch reveal eight peace character values exemplified by Syekh Yusuf: nikatutuinna and ningainna (loving and being loved), kamaseang (caring and compassionate), mallaq and masiriq (fear and shame as moral boundaries), paqrasangang matangkasaka (pursuing truth), bantui na tamaka-makai rannuna pagmaiqna taua (helping to bring joy to others), tamasalai (nonviolence), napassamaturuki (deliberation and consensus), and pamopporang (forgiveness). The implications of these peace character values for guidance and counseling services are identified in the core services, particularly in the areas of personal and social guidance..